2002
DOI: 10.1007/s00415-002-0727-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of functional NMDA-antagonist flupirtine on automatic postural responses in Parkinson's disease

Abstract: Animal studies have demonstrated potent antiparkinsonian and other motor effects of the functional NMDA-antagonist flupirtine and suggest a therapeutic use in Parkinson's disease (PD). In healthy subjects flupirtine decreases the functionally destabilizing medium latency (ML) response following toe-up rotations of a moving platform. Because ML responses are known to be increased in PD, this study examined s the effects of flupirtine on postural responses in patients with PD. During 22 days 21 patients with PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…This was the topic of two trials. The first was a double-blind and placebo-controlled study of flupirtine, a functional antagonist of N-methyl-D-aspartate with a confirmed influence on automatic postural responses in healthy individuals [57]. A single dose of 50 or 100 mg flupirtine failed to improve automatic postural responses to sudden tilts of a supporting platform.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…This was the topic of two trials. The first was a double-blind and placebo-controlled study of flupirtine, a functional antagonist of N-methyl-D-aspartate with a confirmed influence on automatic postural responses in healthy individuals [57]. A single dose of 50 or 100 mg flupirtine failed to improve automatic postural responses to sudden tilts of a supporting platform.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…[6] Antiparkinsonian and other motor effects relying on its NMDA-antagonistic effects were demonstrated. [7] Most frequent ADR in flupirtine treated patients (n=110; 3x 100mg/day) were vertigo (13%) and nausea (9%), but rates of these ADR were significantly lower than in a control group treated with tramadol (n=110) [8]. There are no studies on its long term cerebro-or cardiovascular effects.…”
Section: Dear Sirsmentioning
confidence: 99%
“…(60). Experimentelle Daten sprechen für einen diskreten spezifischen antiparkinsonoiden und Levodopa-potenzierenden Effekt des NMDA-Antagonisten Flupirtin (43,48,51).…”
Section: Tiefe Hirnstimulationunclassified